Performance-Based Agreements : Incorporating Performance-Based Elements into Standard Loan and Grant Agreements, A Technical Guide - EI-Zoghbi, Mayada; Glisovic-Mezieres, Jasmina; Latortue, Alexia (Consultative Group to Assist the Poor/The World Bank, Washington, DC, 2013)
All donors and investors use contracts to establish legal relationships with the partners they fund. Typically, these contracts define the permitted use of the funds and include general suspension or termination clauses. Unfortunately, many agreements do not include project-specific performance targets and do not define sanctions for failure to deliver minimum performance against those targets. This technical guide presents the rationale for the use of performance based agreements (PBAs) and suggests ways to incorporate performance based targets and incentives into existing loan and grant agreements. The focus of this guide is PBAs for retail financial service providers, but some of the advice can be applied to other nonretail projects as well.